2010
DOI: 10.1002/da.20759
|View full text |Cite
|
Sign up to set email alerts
|

Cultural aspects in social anxiety and social anxiety disorder

Abstract: To examine cultural aspects in social anxiety and social anxiety disorder (SAD), we reviewed the literature on the prevalence rates, expressions, and treatments of social anxiety/SAD as they relate to culture, race, and ethnicity. We further reviewed factors that contribute to the differences in social anxiety/SAD between different cultures, including individualism/collectivism, perception of social norms, self-construal, gender roles, and gender role identification. Our review suggests that the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
216
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(249 citation statements)
references
References 69 publications
7
216
1
8
Order By: Relevance
“…Both point of view between previous study and culture showed that head injury become situation which family of patient increase their anxiety due to the condition of their relatives who are in sick. 15 In depth, the results of this study also identified that the anxiety of someone on the condition of patient suffered from pain, is affect to the level of anxiety of family. Data obtained from the results of this study revealed that respondents who identified as mother of patient experienced severe anxiety, unlike respondents as husband and father who are in moderate level of anxiety.…”
Section: Dradjat Prawiranegara Hospital Serang Indonesiamentioning
confidence: 57%
“…Both point of view between previous study and culture showed that head injury become situation which family of patient increase their anxiety due to the condition of their relatives who are in sick. 15 In depth, the results of this study also identified that the anxiety of someone on the condition of patient suffered from pain, is affect to the level of anxiety of family. Data obtained from the results of this study revealed that respondents who identified as mother of patient experienced severe anxiety, unlike respondents as husband and father who are in moderate level of anxiety.…”
Section: Dradjat Prawiranegara Hospital Serang Indonesiamentioning
confidence: 57%
“…The role of sports and the preference for a specific modality can reveal important characteristics of a country's culture, norms and customs. Experience and manifestation of anxiety may be influenced by ethnical and cultural factors due to beliefs on mental diseases, including social context and norms to which an individual is exposed 85 .…”
Section: Discussionmentioning
confidence: 99%
“…In some East Asian, collectivist societies, shame is used openly to control social behavior; feeling it publicly can be a positive attribute. 20 Harmony within the community is valued more than individual accomplishments. A modern, individualistic culture views shame as a sign of failure and considers individual success to be the greatest achievement.…”
mentioning
confidence: 99%